2013
DOI: 10.3897/vz.63.e31435
|View full text |Cite
|
Sign up to set email alerts
|

Population density of the Blanford's fox Vulpes cana in Jordan

Abstract: A survey of the Blanford’s fox was established in Jabal Masuda (Southern Jordan), to increase the knowledge of its density. Live-trapping method was used and capture mark-recapture technique was applied. We captured a total of 27 specimens including nine re-captured specimens. Density was determined using two methods: the Bondrup-Nielsen formula which identified 8.5 individuals per km², and the ArcGIS tools which showed values, between 0.177 to 9 individuals per km². This paper is the first to give measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…It is regarded as not rare in suitable habitat in Saudi Arabia and United Arab Emirates. A capture-mark-recapture study on Jabal Masuda (Jordan) using two analyses found 8.5 animals/km², and 0.177-9/ km², which is higher than reported elsewhere (Eid et al, 2013).…”
Section: Populationmentioning
confidence: 54%
See 2 more Smart Citations
“…It is regarded as not rare in suitable habitat in Saudi Arabia and United Arab Emirates. A capture-mark-recapture study on Jabal Masuda (Jordan) using two analyses found 8.5 animals/km², and 0.177-9/ km², which is higher than reported elsewhere (Eid et al, 2013).…”
Section: Populationmentioning
confidence: 54%
“…All records are from the mountainous periphery of the Arabian Peninsula, except one from the Ibex Reserve in central Saudi Arabia which lies 800 km inland. In Jordan, this species was first recorded in 1996, from the Dana Biosphere Reserve, and has subsequently been recorded in Wadi Rum, Mujib, Petra and Jabal Masuda (Abu Eid et al, 2013). In Oman, this species was first recorded in 1985 when two were trapped on Jebel Samhan in Dhofar, and it has been camera trapped there regularly since then.…”
Section: Range Descriptionmentioning
confidence: 99%
See 1 more Smart Citation